Unusual tumor metastasis from neuroblastoma in a pediatric patient. Case report - de Castro-Rodrigues, Cristóvão M.; Jéssika Mata-Do, Nascimento; Meneses-Santos, Daniela; Sol, Izabella [UNESP] (Publicidad Permanyer, SLU, 2024)
Neuroblastoma is a solid pediatric cancer with heterogeneous clinical behavior. It is classified as an embryonic neuroendocrine tumor, originating from neural crest progenitor cells. As for the clinical signs and symptoms, they can vary from a palpable mass with distension to a substantial dissemination of the tumor with metastases in the hepatic and medullary regions. Surgery plays a key role in the treatment of neuroblastoma, currently, research is developing studies based on immunothe rapies that can improve the prognosis of the disease, but the cure expectations are still reserved, bringing more unfavorable consequences to the case.
Keywords: Face; Jaw; Neoplastic metastasis; Neuroblastoma